Changes in knowledge of mothers who have stunting and not stunting toddlers using booklet, flipchart and poster media - Simanungkalit, Sintha Fransiske; Simanjorang, Chandrayani; Wahyuningsih, Utami; Sofianita, Nur Intania (Alma Ata University Press, 2024)
ABSTRACTBackground: According to 2018 Riskesdas data, the prevalence of stunting in Indonesia increased in 2010 from 35.6% to 37.2% in 2013 and in 2018 it decreased to 30.8%% (1). Research in Dakar, Senegal found that 45% of stunted children came from mothers who had insufficient nutritional knowledge in a group of mothers who did not receive nutritional education (2). Mothers who were given nutritional intervention experienced changes in knowledge and practice in providing food sources of protein and calories. Posters as a media for nutrition education provide changes in knowledge for mothers (3) (4). Booklets, posters and calendars are print media that are often used to convey health education (5).Objectives: The aim of this research defined the difference mothers’knowledge who have stunted and non-stunting toddlers when given booklets, calendars and posters.Methods: This research used a quasi-experimental study and the Wilcoxon test. The inclusion criteria in this study were mothers aged 20-35 years, having children under five, actively participating in Posyandu and willing to take part in research activities for 1 year. The mother's research exclusion criteria were moving from Pasir Putih Subdistrict and not attending Posyandu for 3 consecutive months. The sampling technique uses simple random sampling where maternal data is obtained from attendance at the Posyandu in each RW. Before the research was carried out, the research questionnaire went through a validity and reliability testing stage using computer software.Results: There was a difference in mothers' knowledge before and after being given nutrition education using booklet (pvalue 0.000), using calendar (pvalue 0.000) and using poster media (pvalue 0.000). Conclusions: Nutrition education effectively used as promotive efforts on mother in the prevention of stunting, it can be seen from the improvement of knowledge and nutritional intake before and after being given education